High-performance polysulfide-trapping lithium sulfur battery cathode: cubic Co3O4 catalyst within a nitrogen-doped entangled graphene framework - Manna, Narugopal; Soni, Roby; Young, R. S.; Jervis, Rhodri; Miller, Thomas S. (ChemElectroChem, 2025)
The cycling performance of lithium-sulfur (Li-S) batteries is hampered by polysulfide dissolution which impacts the overall performance of Li-S batteries. Here we report the synthesis and characterization of polysulfide trapping cathode material for Li-S batteries based on Co3O4 nanocubes supported within a nitrogen-doped entangled graphene (Co3O4/NEGF). The highly porous conductive graphene network is shown to facilitate fast electron transport and ion diffusion while the nitrogen dopants and polar Co3O4 offer both abundant active sites for polysulfide conversion while promoting intermediate polysulfide binding. The porous structure allows for high sulfur loading of 76.4 wt % (S@Co3O4/NEGF), while efficiently accommodating volumetric expansion during charge-discharge. The Co3O4/NEGF cathode composite exhibited a high specific capacity of 1143 mAh g-1 at a current density of C/20 and maintained a 79 % reversible capacity after 200 cycles at C/5.